Blurred boundaries: exploring the influence of work-life and life-work conflicts on university teachers’ health, work results, and willingness to teleworking - Sobral, Filipa; Dias-Oliveira, Eva; Morais, Catarina; Hodgson, Julia (Frontiers in Education, 2025)
COVID-19 lockdowns forced organizations to rapidly shift from face-to-face interactions to online platforms, leading to unforeseen challenges. This study retrospectively examines the extreme conditions of teleworking, which blurred the boundaries between home and workspaces, providing a unique opportunity to assess perceptions of work-life and life-work conflicts and their consequences. Data were collected from university teachers through an anonymous online survey (N = 383). A path analysis using IBM SPSS AMOS software assessed the relationship between work-life and life-work conflicts, burnout, performance, and willingness to continue teleworking. Results suggest work-life and life-work conflicts produce different spillovers. Both conflicts significantly contributed to burnout, but only life-work conflict significantly related to perceived performance, and this relationship was negative. Burnout was negatively associated with perceived performance but had no significant relationship with willingness to continue teleworking after lockdowns. Conversely, the relationship between perceived performance and willingness to continue teleworking was significantly positive. These findings emphasize the interplay between work-life and life-work conflicts and their effects on workers’ perceptions. Organizations should consider these dynamics when designing remote work policies to mitigate burnout and enhance employee performance and satisfaction. It is crucial for leadership to take responsibility for prioritizing the well-being of workers and their working conditions, as their actions significantly influence work design, individual and team goals, and the overall organizational climate.